Efeito de produtos fitossanitários sobre larvas de Rhynchophorus palmarum L., 1764 (Coleoptera: Curculionidae) em laboratório - Santos, Samara dos (2016)
Rhynchophorus palmarum is the most harmful weevil pest of coconut palm due to its ability to find hosts from long distances and also to the direct and indirect losses it causes to the crop. Besides this, spores of the fungus that causes the stem bleeding disease have been found over R. palmarum body. Thus, the objective of this work was to evaluate the effect of the insecticide thiamethoxam and its association to the fungicide cyproconazole against R. palmarum larvae under laboratory conditions, aiming at the possible use of these products for managing R. palmarum and the fungal diseases associated to it. Newly-hatched and intermediate-instar larvae were fed with artificial diet containing insecticide or fungicide in the concentrations of 0.1%; 0.5%; 1.0% and 2.0%, and also the mixture of both. Larvae mortality on the treatments was assessed daily, during 48 hours. Means were subjected to analysis of variance and compared by Tukey’s test (P < 0.05). Regression analysis between the different product doses and larval mortality was also performed. Thiamethoxam caused mortality of 100 and 95% to newly-hatched and intermediate-instar larvae, respectively, statistically differing from cyproconazole (50 and 0%, respectively) and from the control (23.2 and 0%, respectively), but not differing from the two products mixture (100 and 92.5%, respectively). Such results point out that newly-hatched larvae are more sensitive than the intermediate-instar ones; that thiamethoxam in the doses here used is toxic to both newly-hatched and intermediate-instar larvae; that cyproconazole in the doses here used is toxic only to newly-hatched larvae; and that cyproconazole, when mixed to thiamethoxam does not improve its toxicity. Linear regression showed that thiamethoxam and its mixture with cyproconazole caused 100% mortality to newly-hatched larvae, and between 80 and 100% and between 90 and 100% to intermediate-instar larvae, respectively, in all tested concentrations. All concentrations were considered high. The thiamethoxam + cyproconazole mixture showed to be promising for the management of R. palmarum and the fungal diseases associated to it in coconut palms.